Assessment of Normal Myelination with Magnetic Resonance Imaging - Welker, Kirk M.; Patton, Alice (Seminars in Neurology, 2012)
White matter myelination is essential to postnatal neurologic maturation and can be accurately evaluated by magnetic resonance imaging (MRI). Accordingly, MRI pulse sequences should be optimized for detection of myelin in young children. T1-weighted images are most useful during the first year of life. These demonstrate myelin-related white matter hyperintensity consequent to increasing cholesterol and galactocerebroside within myelin membranes. T2-weighted images are most useful in later stages of myelination, during which time elaboration of myelin leads to reduction in brain water content with associated T2 hypointensity. Additional information regarding the status of myelination can be obtained from T2-weighted fluid attenuation inversion recovery (FLAIR) and diffusion tensor imaging (DTI) pulse sequences. Clinically useful milestones for assessment of myelination across all these MRI pulse sequences are available as guidelines to image interpretation. Evaluation of myelination status using a combination of T1- and T2-weighted images should be routine in the interpretation of all pediatric brain MRI exams.
Keywords: myelination; development; brain; white matter; infants; magnetic resonance imaging